Association of tissue oxygen saturation levels with skeletal muscle injury in the critically ill - Ryuji Sugiya; Shinichi Arizono; Yuji Higashimoto; Yuta Kimoto; Masashi Shiraishi; Hiroki Mizusawa; Yuichi Tawara; Hironori Shigeoka; Jan Bakker; Koichiro Shinozaki (Scientific Reports, 2024)
Abstract This study aimed to investigate the association between the level of tissue oxygen saturation (StO2) and quadriceps/skeletal muscle dysfunction, measured using the Medical Research Council (MRC) scale and ultrasonography, in critically ill patients. Thirty-four patients hospitalized at the Critical Care Medicine Center of Kindai University Hospital, between January 2022 and March 2023, were enrolled in this study. The StO2 of the quadriceps muscle was measured via near-infrared spectroscopy. Muscle atrophy was measured by the thickness, cross-sectional area (CSA), and echo intensity of the rectus femoris (RF). These values were evaluated every alternate day until 13 days after admission or until discharge, whichever occurred first. Muscle weakness was assessed using the sum score of the MRC scale (MRC-SS), with the patient sitting at bedside. The mean age of the patients was 67.3 ± 15.3 years, and 20 (59%) were men. Seven patients (21%) were admitted for trauma, and 27 (79%) were admitted for medical emergencies or others. The mean score for the MRC-SS was 51.0 ± 7.9 points. RF thickness and CSA significantly decreased after day 7 (p < 0.05). There were no significant changes in StO2 levels during hospitalization. However, there were positive correlations between the nadir StO2 during hospitalization and MRC-SS, and changes in RF thickness and CSA at discharge (r = 0.41, p = 0.03; r = 0.37, p = 0.03; and r = 0.35, p = 0.05, respectively). StO2 in the quadriceps muscle may be useful for predicting muscle atrophy and dysfunction in patients with critical illnesses.